(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Although coronavirus disease (COVID-19) is primarily a respiratory disease, the kidney may be among the target organs of infection with severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). Independently of baseline kidney function, acute kidney injury (AKI) is a common complication of COVID-19, associated with increased mortality and morbidity. Most frequently, COVID-19 causes acute tubular necrosis; however, in some cases, collapsing focal segmental glomerulosclerosis and direct viral tropism of the kidneys have also been documented. AKI secondary to COVID-19 has a multi-factorial origin. Even mild impairment of renal function is an independent risk factor for COVID-19 infection, hospitalisation and mortality. Dialysis patients also carry an increased risk of other severe COVID-related complications, including arrhythmias, shock, acute respiratory distress syndrome and acute heart failure. In such patients, COVID-19 may even present with atypical clinical symptoms, including gastrointestinal disorders and deterioration of mental status. More research is needed on the exact effects of SARS-CoV-2 on the kidneys. Finally, it remains to be proven whether the outcome of patients with kidney disease may be improved with anticipated vaccination programmes.